Histopathological Evaluation of Gall Bladder In Cholecystectomy Specimens in a Tertiary Health Care Centre of Nepal - Pathak, Rakesh; Gupta, M; Poudel, P; Khadka, K (Nepal Medical College Journal, 2020)
Gall bladder is one of the important digestive organ which encountered with different histopathological changes. Different changes in dietary habit, obesity, oral contraceptives, alcohal have shows increased pattern of cholecystitis and cholelithiasis and other pathological findings. Detail examination of gall bladder in cholecystectomy specimen helps to evaluate different histopathological pattern of gall bladder lesion and also help to differentiate non-neoplastic from neoplastic lesion and also helps in further management. This was a cross sectional study done in the Department of Pathology, Nepal Medical College Teaching Hospital, Kathmandu, Nepal, during the study of period of six months (Feburary 2020 to July 2020). A total of 127 patients between 16 years to 63 years with mean age of 40.54±10.88 years. There were 127 cholecystectomy specimens were received during study period and out of which 94 were female and 33 were male. On histopathologial evaluation, chronic cholecystitis was most common findings followed by chronic cholecystitis with cholesterolosis. Other findings were chronic cholecystitis with adenomyosis, chronic cholecystitis with pyloric metplasia, chronic cholecystitis with intestinal metpalsia, chronic cholecystitis with polyp, acute on chronic cholecystitis, Xanthogranulomatous cholecytsitis and adenocarcarcinoma . Median age was 40.54 years. It was concluded that Chronic cholecystitis was the most common histopathologcial findings and the common groups was 41-50 years. Routine examination of cholecystectomy specimens grossly and microscopically is important for patient management Though a very few cases of carcinoma of Gall bladder is seen, it is very important to make sure that all cholecystectomy specimens undergone histopathological examination, with this, we can achieve timely diagnosis and early managements.